2019
DOI: 10.1002/1878-0261.12411
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and Prion protein promote signaling via FOXO3a‐KLF5 resulting in clinical resistance to platinum agents in colorectal cancer

Abstract: Epidermal growth factor receptor ( EGFR ) supports colorectal cancer progression via oncogenic signaling. Anti‐ EGFR therapy is being investigated as a clinical option for colorectal cancer, and an observed interaction between EGFR and Prion protein has been detected in neuronal cells. We hypothesized that Pr P C expression levels may regulate EGFR signaling and that detailed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Pou5f1), and cMyc. Moreover, Atkinson et al reported that EGFR and Prion protein promoted signaling via FOXO3a-KLF5 resulting in clinical resistance to platinum agents in CRC [41]. These data indicate that the drug resistance and recurrence in cancer may involve increased CSC properties.…”
Section: Discussionmentioning
confidence: 97%
“…Pou5f1), and cMyc. Moreover, Atkinson et al reported that EGFR and Prion protein promoted signaling via FOXO3a-KLF5 resulting in clinical resistance to platinum agents in CRC [41]. These data indicate that the drug resistance and recurrence in cancer may involve increased CSC properties.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have shown that KLF5 plays a role in cisplatin resistance in various tumors. In colorectal cancer, KLF5 is predictive for cell line and patient response to platinum agents . In ovarian cancer cell lines, silencing KLF5 by small interfering RNA sensitizes cells to apoptosis induced by cisplatin .…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, KLF5 is predictive for cell line and patient response to platinum agents. 20 In ovarian cancer cell lines, silencing KLF5 by small interfering RNA sensitizes cells to apoptosis induced by cisplatin. 21 A previous study reported that KLF5 knockdown could suppress hypoxia-induced cisplatin resistance in NSCLC, probably via inactivation of the PI3K/Akt/ mTOR pathway; 13 however, the study failed to mention the prognostic value of KLF5 and its underlying roles in the DDR in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of PrP C /P-gp complex has profound effects on tumor survival and aggressiveness, since it markedly reduces the anti-apoptotic activity, while promoting the reversal of PrP C -mediated drug resistance in MDR breast cancer cells [ 135 ]. Furthermore, the direct interaction between PrP C and EGFR is determinant for cisplatin/oxaliplatin resistance in colorectal cancer cells via FOXO3a-Krüppel-like factor 5 (KLF5) signaling, thus contributing to the development of metastases and poor outcome in CRC patients [ 155 ]. Again, PrP C /CD44 interaction promotes chemoresistance and tumor progression in MDR breast cancer cells [ 132 ].…”
Section: The Multi-faceted Role Of Prp C In Canmentioning
confidence: 99%